1995
DOI: 10.1155/mbd.1996.11
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of Zinc With Picolinic and Aspartic Acids Inactivate Free Varicella‐Zoster Virions

Abstract: Zn(ll) picolinate and aspartate, Zn(pic). and Zn(asp)., have been shown to inhibit key steps of the replication of HSV-I. In the present study we describe the effect of Zn(pic). and Zn(asp). on the replication of VZV and on the infectivity of free virions. The experiments are done using BHK-21 cells, a clinical isolate of VZV and Zn-complexes in concentration of 10/M. When Zn-complexes are present during the whole period of infection, the yield of infectious virus progeny decreases up to 98%. The infectivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Vitamin C possesses a reversible concentration-dependent antiviral activity, and the continuous presence of ascorbic acid is needed to keep viruses suppressed ( 11 ) . Similarly, virus replication inhibited by Zn is concentration dependent and reversible in cell cultures ( 50 ) . In the past decade, immune cell activation by intracellular Ca signalling has been well known ( 51 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C possesses a reversible concentration-dependent antiviral activity, and the continuous presence of ascorbic acid is needed to keep viruses suppressed ( 11 ) . Similarly, virus replication inhibited by Zn is concentration dependent and reversible in cell cultures ( 50 ) . In the past decade, immune cell activation by intracellular Ca signalling has been well known ( 51 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from HCMV mentioned above, the effect of zinc on other members of the Herpesviridae family remains unknown because of a lack of clinical data. Mechanistically, zinc ions have been shown to inhibit Varicella-Zoster virus by inactivating free virus in vitro ( 59 ). Both HSV and Varicella-Zoster virus belong to the Alphaherpesvirinae subfamily, reflecting their genetic relatedness, and similar mechanism of inhibition.…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…Zn is known to exhibit a variety of direct and indirect antiviral properties. Previous literature has demonstrated that Zn homeostasis is interconnected with the emergence of infections related to coronaviridae [28] , picornavirus [29] , papilloma virus [30] , rhinovirus [31] , herpes simplex virus [32] , varicella-zoster virus [33] , respiratory syncytial virus (RSV) [34] , human immunodeficiency virus (HIV) [35] and hepatitis C virus (HCV) [36] . Interestingly, Zn displays antiviral properties by a number of physical processes, including virus attachment, penetration, infection, uncoating and replication [37] .…”
Section: The Molecular Basis Of Zinc (Zn) In Biological Systemsmentioning
confidence: 99%
“…Moreover, Zn may potentially inhibit direct membrane fusion of the semliki forest virus by binding to a particular histidine residue present on the viral protein E1 at low endosomal pH [40] . An in vitro study clearly demonstrated that Zn can directly inactivate the free varicella-zoster virus [33] . Zn salts facilitate viral destruction by abolishing viral entry, polyprotein processing, or viral RNA-dependent RNA polymerase (RdRP) activity in a number of other viruses, including SARS-CoV [28] , rhinovirus [31] , HSV [32] , HIV [35] and vaccinia virus [41] .…”
Section: The Molecular Basis Of Zinc (Zn) In Biological Systemsmentioning
confidence: 99%